Cardiorenal 23Na MRI at 7.0 Tesla using a 4/4 channel 1H/23Na RF antenna array - Boehmert, Laura; Kuehne, Andre; Waiczies, Helmar; Wenz, Daniel; Eigentler, Thomas Wilhelm; Funk, Stephanie; von Knobelsdorff-Brenkenhoff, Florian; Schulz-Menger, Jeanette; Nagel, Armin Michael; Seeliger, Erdmann; Niendorf, Thoralf (Magnetic Resonance in Medicine, 2019)
Purpose: Cardiorenal syndrome describes disorders of the heart and the kidneys in which a dysfunction of 1 organ induces a dysfunction in the other. This work describes the design, evaluation, and application of a 4/4-channel hydrogen-1/sodium (1H/23Na) RF array tailored for cardiorenal MRI at 7.0 Tesla (T) for a better physiometabolic understanding of cardiorenal syndrome. Methods: The dual-frequency RF array is composed of a planar posterior section and a modestly curved anterior section, each section consisting of 2 loop elements tailored for 23Na MR and 2 loopole-type elements customized for 1H MR. Numerical electromagnetic field and specific absorption rate simulations were carried out. Transmission field (B+1) uniformity was optimized and benchmarked against electromagnetic field simulations. An in vivo feasibility study was performed. Results: The proposed array exhibits sufficient RF characteristics, B+1 homogeneity, and penetration depth to perform 23Na MRI of the heart and kidney at 7.0 T. The mean B+1 field for sodium in the heart is 7.7 ± 0.8 µT/√kW and in the kidney is 6.9 ± 2.3 µT/√kW. The suitability of the RF array for 23Na MRI was demonstrated in healthy subjects (acquisition time for 23Na MRI: 18 min; nominal isotropic spatial resolution: 5 mm [kidney] and 6 mm [heart]). Conclusion: This work provides encouragement for further explorations into densely packed multichannel transceiver arrays tailored for 23Na MRI of the heart and kidney. Equipped with this technology, the ability to probe sodium concentration in the heart and kidney in vivo using 23Na MRI stands to make a critical contribution to deciphering the complex interactions between both organs.
CRIS-Team Scopus Importer:2019-07-12
Keywords: cardiac MRI; cardiorenal syndrome; MRI; renal MRI; RF coil; sodium